Pembuatan Aset Visual 2D dan 3D Untuk Game Edukasi Interaktif Berbasis Virtual Reality “MolekuLab” - Mira Rosalina; Sinantya Feranti Anindya; Dimas Muhammad Rizki; Yuliana Yuliana; Amanda Firna; Geovanrivo Wibi Morisko Baay (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Chemistry is considered one of the most challenging subjects because most of its concepts are abstract. Based on interviews with teachers, it was found that learning in schools is still limited to the use of markers and whiteboards, and remains teacher-centered. Therefore, a learning medium is needed to help students better understand chemical bonding material, which requires strong visualization. An Interactive Educational Game Based on Virtual Reality can be a potential solution to address this issue. The aim of this study is to produce 2D and 3D visual assets to be integrated into the game. The research subjects were 35 tenth-grade students of SMAS Muhammadiyah 23 Jakarta. The study employed a mixed-method approach, combining qualitative and quantitative methods, using the Multimedia Development Life Cycle (MDLC) framework, which consists of the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Based on the beta testing results, media experts rated the product at 91.67%, categorized as very good. Meanwhile, user responses showed an overall rating of 83.33%, also falling into the very good category in terms of 2D visual assets, 3D visual assets, and learning aspects, indicating that the VR game is relevant to the concept of chemical bonding.